Social Solidarity and Religious Based Islamic Sufism of Khalwatia Samman Thareqah Community - Muhammad Sabiq; Arisnawawi Arisnawawi; Andi Murni; Abdul Malik Iskandar (State Institute of Islamic Studies (IAIN) Salatiga, 2023)
One principle in every Thareqah and deep flow understanding of Sufism that has not been discussed, though it has been attached to various Tarekat flows, both classical and modern, is solidarity social. The present study aims to investigate the solidarity social and identity religious order of Khalwatiyah Samman. By applying a qualitative case study, the data was collected through depth-interview, observation, and documentation review.The study participants applied a purposive technique by pre-determining the participants’ characteristics to obtain the data. The results show that the Congregation of the Khalwatiyah Samman, Maros, represents solidarity social-based Islamic spiritualism. The harmony between the members is the main characteristic of the community. Pilgrims’ submission to the caliph figure becomes socially fundamental for integrity and harmony to prevent disintegration. Two fundamental factors maintain this charismatic leadership, genealogy and scientific genealogy. Both give legitimacy to a caliph’s leadership in a Tarekat. People who want to join the community must pass the first and essential stage, Bai’at. Some stages follow it to maintain solidarity, such as congregational prayer, recitation, and other wider activities. The Congregation of Khalwatiyah Samman is symbolically characterized by wearing a Turban. The Turban has its own story and philosophical value itself. The study implies information on social integration from various stratum and public differences based on spirituality.